2021
DOI: 10.1371/journal.pone.0250656
|View full text |Cite
|
Sign up to set email alerts
|

Ideological biases in social sharing of online information about climate change

Abstract: Exposure to media content is an important component of opinion formation around climate change. Online social media such as Twitter, the focus of this study, provide an avenue to study public engagement and digital media dissemination related to climate change. Sharing a link to an online article is an indicator of media engagement. Aggregated link-sharing forms a network structure which maps collective media engagement by the user population. Here we construct bipartite networks linking Twitter users to the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Such many-to-many interactions can be modeled as a network by building bipartite, a hypergraph or, more broadly, higher order models [53]. Yet, a large number of backbone extraction models work directly on projected networks where edges are added to represent interactions among pairs of users [10,12,19,20,[56][57][58]. This is the case of Disparity Filter, Noise Corrected, among others [33,36,77].…”
Section: Step 1-building a Network Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Such many-to-many interactions can be modeled as a network by building bipartite, a hypergraph or, more broadly, higher order models [53]. Yet, a large number of backbone extraction models work directly on projected networks where edges are added to represent interactions among pairs of users [10,12,19,20,[56][57][58]. This is the case of Disparity Filter, Noise Corrected, among others [33,36,77].…”
Section: Step 1-building a Network Modelmentioning
confidence: 99%
“…By applying a probabilistic backbone extraction method called Disparity Filter [ 77 ], they revealed the formation of communities of users that cross the boundaries of existing groups, favoring dissemination of information at large [ 76 ], including misinformation [ 21 ]. Similarly, different backbone extraction methods have been applied to uncover patterns describing the dynamics of online discussions on Instagram, Twitter, Facebook and Reddit [ 19 , 22 , 23 , 56 58 , 78 , 79 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Political orientation, eco-skepticism, and eco-anxiety may also be related. Cann, Weaver and Williams (2021) conducted social media sharing analysis of climate change information and found that levels of climate skepticism were associated with political ideology and information network polarization. As climate change continues to affect the planet, ecoanxiety and broad-scale research to understand the demographic and information exposure factors associated with it have increasing importance.…”
Section: Introductionmentioning
confidence: 99%
“…Political orientation, eco-skepticism, and eco-anxiety may also be related. Cann, Weaver and Williams (2021) conducted social media sharing analysis of climate change information survey, respondents answered questions regarding their demographics. At the end of the survey, respondents were thanked for their participation.…”
Section: Introductionmentioning
confidence: 99%